The creation of the play With Love, From Inside by The Dropped Keys Theatre Company: an interview with Ashley Lucas (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
In this interview, Ashley Lucas, Professor at the University of Michigan and a member of the Prison Creative Arts Project (PCAP) and The Dropped Keys Theatre Company, shares aspects surrounding the creation, performances, and touring of the play With Love, From Inside (recently translated into Portuguese as Daqui de dentro, com amor.
Keywords: theatre and prison; theatre pedagogy; playwriting